2022
DOI: 10.7554/elife.78085
|View full text |Cite
|
Sign up to set email alerts
|

Mir204 and Mir211 suppress synovial inflammation and proliferation in rheumatoid arthritis by targeting Ssrp1

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease characterized by synovial hyperplasia. Mir204 and Mir211 are homologous miRNAs with the same gene targeting spectrum. It is known that Mir204/211 play an important role in protecting osteoarthritis development; however, the roles of Mir204/211 in RA disease have not been determined. In the present study, we investigated the effects and molecular mechanisms of Mir204/211 on synovial inflammation and hyperproliferation in RA. The effects of Mir204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…MiR-204 and miR-211, two homologous miRNAs with the same target genes, were reported to protect against OA progression [157]. Wang and coworkers continued to determine the effects of two miRNAs on synovial hyperplasia and inflammation [158]. First, they found that expression of miR204/211 was dramatically decreased in synoviocytes of CIA mice, affecting cell migration, apoptosis, proliferation, and inflammatory responses.…”
Section: Ncrnas In Rheumatoid Arthritismentioning
confidence: 99%
“…MiR-204 and miR-211, two homologous miRNAs with the same target genes, were reported to protect against OA progression [157]. Wang and coworkers continued to determine the effects of two miRNAs on synovial hyperplasia and inflammation [158]. First, they found that expression of miR204/211 was dramatically decreased in synoviocytes of CIA mice, affecting cell migration, apoptosis, proliferation, and inflammatory responses.…”
Section: Ncrnas In Rheumatoid Arthritismentioning
confidence: 99%
“…Wu et al, (2021) have reported the change in the expression level of miRNA-330-3p in cartilage injury and bone deformities [28]. Previous studies have reported the involvement of miRNA-103a-3p, miRNA-10a-5p, miRNA-204-3p, miRNA-330-3p, and miRNA-19b in synovial PLOS ONE inflammation, cartilage injury, and in inflammatory joint disorder [23][24][25][26][27][28]. No study has been published concerning involvement of exosomal miRNAs, miRNA-103a-3p, miRNA-10a-5p, miRNA-204-3p, miRNA-330-3p, and miRNA-19b in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al, (2015) have reported that miRNA-103a-3p controls bone development and inflammation by targeting the RUNX2 gene and acts as the first mechanosensitive microRNA to rescue osteoporosis [26]. Wang et al, (2022) has identified the structure-specific recognition protein 1 (Ssrp1) as the target site of the miRNA-204-3p, and deregulation of miRNA-204-3p results in excessive cellular proliferation and synovial inflammation and ultimately leads to RA [27]. Wu et al, (2021) have reported the change in the expression level of miRNA-330-3p in cartilage injury and bone deformities [28].…”
Section: Introductionmentioning
confidence: 99%